Investigating the Relationship between Screen Time and Green Time with Academic Engagement and Academic Performance - Davod Ghaderi; Omid Ebrahimi Shahed (Journal of Modern Psychology)
Objective: This study investigated the relationship between screen time and green time with academic engagement and academic performance of secondary school students in Tabriz city.Methods: The present study was part of cross-sectional and descriptive studies of the correlation and prediction type. Three hundred eighty-five people from Tabriz secondary school students were selected in the first semester of the 2022-2023 academic year by multi-stage cluster sampling based on Morgan's table. All sample members completed Reeve's academic engagement scale (AES) and Screen Time Questionnaire (STQ). The student's GPA was considered their academic performance and was evaluated by adding two questions to the research questionnaires of the green time variable. The collected data were analyzed using Pearson's correlation coefficient, simultaneous regression, and SPSS23 statistical software.Results: The results showed a negative and significant relationship between screen times, the dimensions of academic engagement, and the student's GPA. It was also found that there is a positive and significant relationship between green time and the dimensions of academic engagement (except the emotional involvement dimension) and students' GPA. Screen time and green time significantly contributed to explaining students' academic engagement and academic performance.Conclusion: The results highlighted the importance of screen and green time in educational variables.